2010
DOI: 10.1007/978-1-4419-6366-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Performance of Striated Muscle

Abstract: The single muscle fibre preparation provides an excellent tool for studying the mechanical behaviour of the contractile system at sarcomere level. The present article gives an overview of studies based on intact single fibres from frog and mouse skeletal muscle. The following aspects of muscle function are treated: 1.The length-tension relationship. 2. The biphasic force-velocity relationship. 3. The maximum speed of shortening, its independence of sarcomere length and degree of activation. 4. Force enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…With the growing evidence from skeletal muscle for the role of Ca 2+ in the Bmanipulation^of length-tension curves, it was apparent that factors other than the degree of myofilament overlap could explain the striking differences in length-tension curves and the enigmatic length dependence of heart muscle. We noted that later findings from (Edman 2010) showed that the length-tension curve in skeletal muscle exhibits a much smoother shape than proposed by Gordon et al (1966). Specifically, the length-tension relationship does not have a pronounced plateau region at 2.0-2.2 μm sarcomere length, while the descending limb was also non-linear.…”
Section: Rank-starling Relationshipmentioning
confidence: 63%
“…With the growing evidence from skeletal muscle for the role of Ca 2+ in the Bmanipulation^of length-tension curves, it was apparent that factors other than the degree of myofilament overlap could explain the striking differences in length-tension curves and the enigmatic length dependence of heart muscle. We noted that later findings from (Edman 2010) showed that the length-tension curve in skeletal muscle exhibits a much smoother shape than proposed by Gordon et al (1966). Specifically, the length-tension relationship does not have a pronounced plateau region at 2.0-2.2 μm sarcomere length, while the descending limb was also non-linear.…”
Section: Rank-starling Relationshipmentioning
confidence: 63%
“…However, in our single myofiber model, we are generally more focused on the pure hypoxic effect on a single skeletal myofiber, since any myoglobin in our model could potentially cause a buffering effect, which may delay or interfere with the required low oxygen condition. In addition, although the frog fiber used in the current study lacks myoglobin, there is a great level of correlation between the frog and mammalian myocytes (9), and these two share a substantial similarity in typical skeletal muscle physiology, especially concerning mitochondrial and contractile function. Xenopus fibers are frequently used as a representative model for analyzing skeletal muscle function and metabolism (34,47).…”
Section: Discussionmentioning
confidence: 99%
“…Within the sarcomere, the interaction between the sarcomeric proteins (e.g., actin and myosin) provides the fundamental unit to generate force production. More specifically, the mechanical properties of diaphragm muscle fibers are characterized by the relationship between cytosolic free calcium, crossbridge attachment/cross-bridge cycling rate, and sarcomere length (25). It follows that any factor that influences one or more of these variables can impact diaphragm muscle force generation.…”
Section: Mechanisms Responsible For Mv-induced Diaphragm Contractile mentioning
confidence: 99%
“…In reference to the specific diaphragm muscle proteins that are degraded during MV-induced sarcomere damage, it is established that both titin and myosin play an essential role in skeletal muscle force production (25,113). It follows that an MV-induced loss of titin or myosin from diaphragm muscle fibers could result in contractile dysfunction.…”
Section: R471mentioning
confidence: 99%